Lasten jalkapallovalmentajien käsityksiä liikuntakasvatuksen toteutumisesta valmennuksessa sekä valmennusosaamisen kehittymisestä - Korhonen, Otso (2025)
In this master's thesis, the aim was to investigate the perceptions of children's football coaches regarding the implementation of physical education in their coaching and how the training provided by the Football Association supports the development of the coach's psychosocial coaching skills. Additionally, it examined the factors that support and hinder the implementation of physical education in coaching, as well as other factors besides the Football Association's training that support the development of coaching skills.